Numerical Estimation of Film Thickness With an Air-Assisted Spray Gun - BAYTOK, Yusuf Mert; EREK, Aytunç; SAF, Orçun (Engineering Transactions, 2023)
The main goal of this study is to present the effects of spraying parameters on the numerical evaluations of the fundamental behaviors of an air-assisted spray gun during the formation of child droplets in the spray flow field and material deposition on the target surface. For this purpose, first of all, the air-assisted spray gun geometry was created using the Solidworks software. Then, a computational domain with a 3D, unstructured grid structure was generated using the ANSYS-Workbench meshing tool. Numerical calculations were conducted using ANSYS-Fluent 2020-R2 commercial software. Different breakup models and their effects on the child droplet size were investigated. By coupling the Taylor analogy breakup (TAB) model and discrete phase model (DPM), the droplet size, trajectory, and coating thickness calculations were made under different atomizing air pressures. Also, the effects of spraying distance and droplet size on coating thickness and the critical Weber (We) number on the atomized particle diameter and particle speed were investigated. The results show that with the increase in atomizing air pressure, droplet sizes decrease and the film thickness on the center of the target surface and droplet speeds increases. Also, increasing the critical Weber number makes it more difficult to atomize the droplets.